2018
DOI: 10.20944/preprints201810.0759.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacy-Based Travel Health Services in the United States

Abstract: Pharmacists and pharmacies are highly visible and accessible to the public and have long been regarded as a source for immunization services in the United States. As international travel continues to increase and grow in popularity in this country, there is a pressing need for expanded access to preventative health services including routine and travel vaccinations and medications for prophylaxis or self-treatment of conditions that may be acquired overseas. In the United States, the scope of pharmacy practice… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Four studies mentioned the vaccination services in the pharmacies. [ 6 10 11 24 ] The study by Todd et al . in the UK used the geographic information system and reported that people have access to the pharmacies more than the general physicians.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies mentioned the vaccination services in the pharmacies. [ 6 10 11 24 ] The study by Todd et al . in the UK used the geographic information system and reported that people have access to the pharmacies more than the general physicians.…”
Section: Resultsmentioning
confidence: 99%
“…The study reported that the vaccination by the pharmacies is effective in preventing the transmission of diseases from other countries to the US. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expanding the work functions of pharmaceutical workers and increasing the subjects of pharmaceutical consultation and the list of medical services are actively studied around the world [1][2][3]. So, in the USA, the possibility of informing the population about immunization, including tourist vaccinations, the use of drugs for the prevention or self-treatment of diseases, and pharmaceutical care [4] is discussed. The pharmaceutical specialist is a reliable and accessible source of information, which often leads to violations of the rules and procedures for the sale of drugs.…”
Section: Introductionmentioning
confidence: 99%